Swallowing Problems among Community-Dwelling Elderly in Northeastern Thailand - Sarintip Chaleekrua; Kanya Janpol; Pattra Wattanapan (SAGE Publishing, 2021)
Introduction/objectives Aging brings deterioration in many organs involving in swallowing, such as, oropharyngeal muscle weakness, decreased salivation, multiple teeth loss, decreased oral sensation, and delayed swallowing response. There are no official statistics and systematic records of swallowing problems in Thailand's healthy elder populations. Therefore, this study aimed to determine the prevalence of swallowing problems among a Thai healthy elder population. Methods A survey of 874 elders was conducted at Community Hospitals in region 7 of the Thai National Health Security Office from September to November 2019. All participants were interviewed using a questionnaire focused on, screening for swallowing problems using a 10-item Eating Assessment Tool (EAT-10) and questions about participants' physical and oral health behaviors. Results Sixty-six percent of the participants were women and 34% were males, with mean age 69.70 ± 6.79 years. Of these, 11.4% had swallowing problems. The most common swallowing problems were food sticking in the throat, effort on swallowing and choking. Age and having an underlying disease were found to be statistically significantly associated with dysphagia, whereas gender was not associated with dysphagia. Conclusions The prevalence of swallowing problems among Thai healthy community-dwelling elders was assessed as about 11%. Early identification and early intervention for swallowing problem is necessary for promoting health and quality of life of our growing elderly population.